Analysis of Mathematics Learning Needs Using Animated Videos Based on Discovery Learning in Junior High Schools - Permadani, Tri Nova Ayu; Andayani, Sutrisni; Rahmawati, Dwi (International Journal of Multidisciplinary Research of Higher Education, 2025)
Video animation plays an important role in learning mathematics because it can present abstract concepts visually and interactively. In addition, the delivery of interesting material through animation can increase students' understanding and interest in learning. Therefore, this study aims to analyze the extent of students' needs in learning mathematics using discovery learning-based animated videos in junior high school. This research uses a quantitative method with a survey approach, where data is obtained through a questionnaire designed to collect information about students' needs for animated video-based learning media. Respondents in this study were thirty students from one of the junior high schools in Indonesia. Respondents were selected using purposive sampling technique. In the process of data analysis, this research utilizes Microsoft Excel to organize, process, and present data in the form of tabulations, tables, and diagrams. The analysis technique used is descriptive quantitative which includes the calculation of mean (average), median, and percentage. This statistical calculation is done to see the tendency of students' answers to the questions given in the questionnaire, so that an overview can be obtained about the extent of their needs for the use of Discovery Learning-based animated videos in learning mathematics. The findings are expected to be the basis for developing more effective and interesting animated video-based learning media. In addition, this research can also provide insight for educators in designing learning strategies that suit the needs of students, so as to improve students' understanding and learning outcomes.